Keefektifan Media E-Book Berbasis STEM Pada Materi Urban Heat Island (UHI) untuk Meningkatkan Kemampuan Literasi Sains Peserta Didik Kelas X SMA - Aghniya' Maulia Meyrtha Rahanli; Rinie Pratiwi Puspitawati (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2026)
Science literacy is defined as the ability to analyze, explain phenomena, and draw conclusions based on relevant scientific evidence. The low level of science literacy among students in Indonesia is influenced by the lack of contextual and interactive learning media. The development of Science, Technology, Engineering, and Mathematics (STEM) based learning media is urgently needed to improve science literacy skills by connecting learning to real-world problems in the environment. This study aims to describe the effectiveness of STEM based e-book media on Urban Heat Island (UHI) material to improve science literacy skills. The e-book media was designed to integrate the disciplines of science, technology, engineering, and mathematics, referring to science literacy indicators, including a. explaining phenomena scientifically; b. evaluating scientific investigations; and c. interpreting data scientifically (OECD, 2019). The 4D research model (define, design, develop, and disseminate) was used on 28 high school students. The effectiveness of the e-book media was declared effective based on the achievement of indicators based on STEM Zone activities with a score of 84.07, the highest category on the “evaluating scientific investigations” indicator. The pre-test and post-test results showed science literacy skills with a score of 93.62, the highest category in the indicator “explaining phenomena scientifically.” The sensitivity items obtained 0.51 (sensitive), influenced the learning effect. Therefore ,STEM-based e-book media is effectively used to improve the science literacy skills of grade X high school students